Factors that influence female entrepreneurship in the European Union - Hayrapetyan, Lilit (2017)
This research work aims to discuss the gender issue concerning entrepreneurship in European Union countries in a period of nine years, from 2007 to 2015, identifying the factors which drive females to be entrepreneurs. The study mainly concentrates on identifying and quantifying the personal, social, political and economic features which are motivating women, to be entrepreneurs, as well as the main difficulties they feel during the process of business creation. In order to explore the entrepreneurial activity across a set of developed countries the econometric methodology of panel data (in particular the fixed effects and random effects models) is applied to a data set of entrepreneurial statistical indicators calculated and made available by the Global Entrepreneurship Monitor.